Clinical manifestations and seasonal occurrence of patients with dengue hospitalized at Dhaka city of Bangladesh in 2021 (Dhaka University Journal of Biological Sciences, 2024)
For the past few years, the intensity of dengue in Bangladesh has been rising. The current study was done among 533 dengue patients hospitalized in 2021 in Dhaka to observe the different aspects of clinical manifestations and seasonal occurrence of dengue. Due to COVID-19 restriction, hospital entry and face-to-face interview of the patients was not possible. Hence, contact numbers of the hospitalized dengue patients were collected from Directorate General of Health Services (DGHS) and patients were interviewed over the phone. Out of 533 patients, majority were from Dhaka south city corporation (DSCC) (53.7%), had a monthly household income of 30001≥ BDT (67.4%), and lived in small sized families (76.9%). High fever (p=0.013), headache (p